2016
DOI: 10.1111/ggi.12718
|View full text |Cite
|
Sign up to set email alerts
|

Predictive factors of mortality and deterioration in performance of activities of daily living after hip fracture surgery in Kagoshima, Japan

Abstract: Patients with poor activities of daily living performance at the time of hospital discharge were likely to show poor functional recovery and a high 1-year postoperative mortality. Geriatr Gerontol Int 2017; 17: 391-401.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
31
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(37 citation statements)
references
References 42 publications
(72 reference statements)
2
31
2
Order By: Relevance
“…Ishidou et al . presented a decline at discharge from hospital (50 points), and a recovery after 12 months (75 points) . Long‐term follow up regarding the progression is still missing.…”
Section: Discussioncontrasting
confidence: 78%
See 4 more Smart Citations
“…Ishidou et al . presented a decline at discharge from hospital (50 points), and a recovery after 12 months (75 points) . Long‐term follow up regarding the progression is still missing.…”
Section: Discussioncontrasting
confidence: 78%
“…and Ishidou et al . Both studies showed a high pre‐facture Barthel Index score (96 points vs 90 points) . Gherardini et al .…”
Section: Discussionmentioning
confidence: 92%
See 3 more Smart Citations